Dispersive solid phase extraction based on reduced graphene oxide modified Fe3O4 nanocomposite for trace determination of parabens in rock, soil, moss, seaweed, feces, and water samples from Horseshoe and Faure Islands - Tekin, Zeynep; Karlidag, Nazime Ebrar; Ozdogan, Nizamettin; Kocoglu, Elif Seda; Bakirdere, Sezgin (ELSEVIER, 2022)
This study reports an efficient, green, sensitive and simple analytical protocol for trace determination of methyl paraben, ethyl paraben, propyl paraben, butylparaben and benzyl paraben by high-performance liquid chromatography-ultraviolet detection (HPLC-UV). The analytes were preconcentrated using an ultrasonication supported (US) dispersive solid phase extraction (DSPE) method based on reduced graphene oxide (rGO) modified iron nanoparticles (US-Fe3O4@rGO-DSPE). A reversed-phase C18 column and an isocratic elution program comprising of 20 mM phosphate buffer (pH 4.50) and acetonitrile(58:42, v/v) were used to elute and separate the analytes for detection. The limits of detection determined for the analytes were very low and were in the range of 0.02 - 0.16 ng mL-1. The coefficients of determination obtained for the analytes ranged from 0.9973 to 0.9998, and this validated good linearity of the method.Percent relative standard deviations obtained in the range of 2.5 - 10.6% verified the method's high intraday repeatability. Accuracy of the proposed method was assessed with spiking experiments performed on complex sample matrices. Percent recoveries calculated for spiked soil, artificial seawater and seaweed samples were in acceptable ranges of 95 - 121%, 87 - 117% and 85 - 111%, respectively. These figures of merit suggest that HPLC-UV coupled with the US-Fe3O4@rGO-DSPEmethod is suitable for the determination of parabens in Antarctic samples.
Keywords: Parabens; Reduced graphene oxide; Magnetic nanoparticles; High performance liquid chromatography; Antarctica; PERSISTENT ORGANIC POLLUTANTS; WALLED CARBON NANOTUBES; GAS-CHROMATOGRAPHY; IMPRINTED POLYMER; REMOVAL; MICROEXTRACTION; PRESERVATIVES; RESIDUES; Engineering; Environmental Sciences & Ecology